Is Students’ Speaking Participation Related to Students’ Personality and Gender?: Observations at an Indonesian University - Maziyyatul Muslimah (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
Pedagogically, students will gain more when they engage in a discussion actively rather than as passive observers. Therefore, active participation in class is a prominent aspect of enhancing students’ competencies. Additionally, there are several studies of personality traits and gender differences proven to influence students’ participation, which encourage the author to observe the relationship between students’ speaking participation, personality traits, and gender differences. The author also investigated other factors that influence students’ participation in classroom discussions based on the students’ perspectives. Using mixed methods empirical research, the results of this study reveal that introverted students have a slightly higher participation rate than extroverted students which contradicts findings of some previous research. Meanwhile, investigation of gender shows that the average of male students’ speaking participation is relatively higher than females. Further investigation of factors that possibly influence students’ engagement indicates a strong relationship between English education background and students’ speaking participation. Thesee findings are expected to contribute to the literature for higher education researchers interested in understanding factors influencing students’ participation and as a consideration for higher education practitioners to enhance students’ engagement in class activities.